Emerging Trends and Applications in Information Communication Technologies Second International Multi Topic Conference, IMTIC 2012, Jamshoro, Pakistan, March 28-30, 2012. Proceedings - Chowdhry, Bhawani Shankar; Shaikh, Faisal Karim; Hussain, Dil Muhammad Akbar; Uqaili, Muhammad Aslam; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Second International Multi-topic Conference, IMTIC 2012, held in Jamshoro, Pakistan, in March 2012. The 51 revised full papers presented were carefully reviewed and selected from 205 submissions. The papers address topics from information communication technologies.
Keywords: Computer science; Computer Communication Networks; Data protection; Computer software; Information storage and retrieval systems; Artificial intelligence; Computer Science; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Systems and Data Security